A STUDY THE RELATIONSHIPS AMONG CHEMICAL AND PHYSICAL PROPERTIES OF MILK COMPONENTS OF NATIVE AND MARAZ GOAT BREEDS - MOHAMMED, ISSA M. (Journal of Duhok University, 2022)
The relationship between milk components is very important to build an equation of prediction for the future measurements. Data utilized in this study were obtained from Native and Maraz does bred at private farm in Sumail district/ Duhok governorate/ Kurdistan region of Iraq. A total of 102 samples of milk were collected directly from the udder after neglecting the first few drops to determine Physico-chemical components of milk like Protein% (P%), Fat% (F%), Lactose% (L%), Solid Non-Fat (SNF%), Freezing Point (FP), PH, Specific Gravity and ZP) by different Eko milk apparatuses. The overall means of P%, F%, L%, SNF%, FP, PH, Specific Gravity and ZP for Native goat were 3.43, 3.48, 4.33, 8.51, -0.52, 6.37, 1.03 and 2.30 while these averages for Maraz Goat were 3.48, 3.54, 4.32, 8.55, -0.53, 6.32, 1.03 and 2.32, respectively. Results revealed that it may predicting SNF % from either specific gravity or FP in Native goat milk; while it can predict SNF % from both specific gravity and FP in Maraz goat milk in addition to the possibility of prediction lactose % from specific gravity only. The highest determination coefficient (R2) value for the best prediction equation in Native goat milk was found for predicting SNF % from simple linear regression (0.84); while the best one for the milk of Maraz was achieved for predicting SNF% from multiple linear regression (0.67)